7T MRI cerebral leptomeningeal enhancement is common in relapsing-remitting multiple sclerosis and is associated with cortical and thalamic lesions - Zurawski, Jonathan; Tauhid, Shahamat; Chu, Renxin; Khalid, Fariha; Healy, Brian C; Weiner, Howard L; Bakshi, Rohit (Multiple sclerosis, 2020)
Meningeal inflammation may contribute to gray matter (GM) involvement in multiple sclerosis (MS) and is proposed to manifest as magnetic resonance imaging (MRI) leptomeningeal enhancement (LME). To investigate how LME relates to GM lesions in relapsing-remitting multiple sclerosis (RRMS) at 7T. A total of 30 RRMS subjects (age (mean ± standard deviation (SD)): 44.0 ± 11.3 years, 93% on disease-modifying treatment) and 15 controls underwent gadolinium-enhanced three-dimensional (3D) MP2RAGE (magnetization-prepared 2 rapid gradient-echo) and fluid-attenuated inversion recovery (FLAIR) MRI. LME, cortical lesions (CLs), thalamic lesions (TLs), and white matter (WM) lesions were expert-quantified. Wilcoxon rank-sum, two-sample -tests, Spearman correlations, and regression models were employed. Two-thirds (20/30) of MS subjects and 1/15 controls (6.7%) had LME. LME+ MS subjects had 2.7 ± 1.5 foci, longer disease duration (14.9 ± 10.4 vs. 8.1 ± 5.7 years, = 0.028), increased CL number (21.5 ± 12.6 vs. 5.5 ± 5.0, < 0.001) and volume (0.80 ± 1.13 vs. 0.13 ± 0.13 mL, = 0.002), and increased TL number (3.95 ± 2.11 vs. 0.70 ± 1.34, < 0.001) and volume (0.106 ± 0.09 vs. 0.007 ± 0.01 mL, < 0.001) versus LME- subjects. LME focus number correlated more highly with CL ( = 0.50, = 0.01) and TL ( = 0.81, < 0.001) than WM lesion ( = 0.34, > 0.05) volume. Similar LME-CL number associations were observed in unadjusted and WM lesion-adjusted comparisons (both < 0.001). Cerebral LME is common in RRMS at 7T and is independently associated with GM injury. We hypothesize that cerebrospinal fluid (CSF)-related inflammation links cortical and thalamic injury.